2021
DOI: 10.1186/s13018-021-02738-2
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0045714/miR-331-3p interaction affects IL-1β-evoked human articular chondrocyte injury through regulating PIK3R3 in a ceRNA regulatory cascade

Abstract: Background Osteoarthritis (OA) is characterized by joint pain and joint function limitation. Hsa_circ_0045714 (circ_0045714) is a novel OA-related circular RNA. However, its repertoire remains to be further clarified in joint chondrocytes. Methods RNA and protein expression levels and inflammatory factor levels were detected by real-time quantitative polymerase chain reaction, western blotting and enzyme-linked immunosorbent assay. Cell proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“… CircRNAs are identified to be associated with the pathogenesis of OA [ 22 ]. Hsa_circ_0045714 level downregulation reduced IL-1β-evoked OA chondrocyte injury [ 23 ]. Silencing circ_0001846 alleviated cell apoptosis and inflammation in IL-1β-induced OA progression [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… CircRNAs are identified to be associated with the pathogenesis of OA [ 22 ]. Hsa_circ_0045714 level downregulation reduced IL-1β-evoked OA chondrocyte injury [ 23 ]. Silencing circ_0001846 alleviated cell apoptosis and inflammation in IL-1β-induced OA progression [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, circ_0134111 promoted OA chondrocyte damage by inhibiting miR-224-5p to induce overexpression of CC motif ligand 1 (CCL1) [ 33 ]. Circ_0045714 increased phosphoinositide-3-kinase regulatory subunit 1 (PIK3R1) level to regulate IL-1β-stimulated chondrocyte injury via serving as a ceRNA of miR-331-3p [ 23 ]. In this study, miR-142-5p directly targeted TCF4 and circ_0005526 led to upregulation of TCF4 expression via targeting miR-142-5p.…”
Section: Discussionmentioning
confidence: 99%
“… Li et al (2017) found that circ 0045714 could regulate the synthesis of ECM by inhibiting the transcriptional activity of miR-193b and promoting the expression of miR-193b target gene insulin-like growth factor 1 receptor (IGF1R) ( Li et al, 2017 ). Ding et al (2021) .up found that circ 0045714 plays a protective role in IL-1β-induced chondrocyte injury by targeting and inhibiting miR-331-3p and then upregulating PIK3R3, which is manifested in alleviating chondrocyte apoptosis, inflammatory response and ECM degradation ( Ding et al, 2021 ).…”
Section: The Role Of Ncrnas In Osteoarthritis and Its Interaction Wit...mentioning
confidence: 99%
“…Phosphoinositide 3-kinase (PI3K) regulatory subunit 3 (PIK3R3) is an inhibitor of PI3K [ 19 ] in the PI3K/AKT pathway, and is intimately related to OA pathogenesis [ 20 , 21 ]. PIK3R3 was confirmed to be downregulated in OA knee cartilage and participated in OA progression [ 22 , 23 ]. Here, we showed that circ_0044235 could bind to miR-375, and miR-375 could target PIK3R3.…”
Section: Introductionmentioning
confidence: 99%